Mitigation Effort for Sustainable Mangrove Management Towards a Low Emission Indonesia: Study at Arboretum Mangrove Kolak Sekancil - Purwendah, Elly Kristiani; Triana, Ikama Dewi Setia; Pudyastiwi, Elisabeth; Kusumaningsih, Oti; Wahyono, Daniel Joko (Universitas Muhammadiyah Purwokerto, 2025)
Krida Wana Lestari Farmer Group supports the Indonesian government's policy to reduce carbon emissions as a community obligation to participate in managing the environment, as the purpose of the ratification of the Paris Agreement ( Law Number 16 of 2016 on the Ratification of Paris Agreement to the United Nations Framework Convention on Climate Change). The farmer group successfully built an edu-tourism area, the Segara Anakan Lagoon Conservation Mangrove Arboretum (Kolak Sekancil). This farmer group cultivates and utilizes mangrove products for life and has succeeded in increasing mangrove density in the Cilacap Sea Village Area with an area of approximately 6,2126.28 Ha. Mangrove farming by farming communities is a form of community participation regulated in Article 65 Paragraph (4) Law Number 32 of 2009 on Environmental Protection and Management The legal institution of this community is formally supported by the village government with Village Regulation No. 7 of 2022 concerning Mangrove Ecosystem Management in the Segara Anakan Region of Cilacap.